Comparison of Post Vaccination Antibody Levels for Coronavirus Disease 2019 (COVID-19) between Survivors and Non-Survivors of COVID-19 - Yuniza; Nova Kurniati; Zen Ahmad; Nurmalia Purnama Sari; Msy Rita Dewi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2023)
Background: The COVID-19 vaccine is useful for protecting the body by causing or stimulating specific immunity in the body. COVID-19 survivors are a group of individuals who have been exposed to COVID-19 and have successfully recovered from COVID-19 infection. Exposure to COVID-19 causes the activation of memory cells and anti-SARS-CoV-2 IgG antibodies. In contrast to individuals who have never been exposed to COVID-19, the bodies of individuals who are not COVID-19 survivors have not had the experience of exposure to COVID-19, which causes the absence of memory cells and anti-SARS-CoV-2 IgG antibodies. This study is one of the first studies to explore differences in anti-SARS-CoV-2 IgG antibody levels in survivors and non-survivors of COVID-19 at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This was an analytic observational study with a cohort approach. A total of 136 research subjects participated in this study. Observation of anti-SARS-CoV-2 IgG levels was carried out before vaccination, weeks 2, 12, and 24. Data analysis was carried out using SPSS univariate and bivariate. Results: The COVID-19 survivors group consistently from the time they were vaccinated, weeks 2, 12, and 24 showed a relatively higher average anti-SARS-CoV-2 IgG level than the non-COVID-19 survivors' group. The group of survivors of COVID-19 shows a trend of decreasing average anti-SARS-CoV-2 IgG levels over time. In contrast to the non-survivor group of COVID-19, which showed a trend of increasing anti-SARS-CoV-2 IgG levels. Conclusion: There were differences in anti-SARS-CoV-2 IgG levels between the COVID-19 survivor group and non-survivor COVID-19 group at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.